Hubungan Antara Disiplin Belajar Dengan Prestasi Belajar Siswa Kelas VII MTsN Megaluh Jombang - Ahmad Sukron Hamdan; Muhtadi; Adibah Jauhari (Arsy : Jurnal Studi Islam, 2018)
Discipline is the basis of a person's success in running an activity. A student will obtain achievement in learn best when they are disciplined in learning. Logically the success of all activities can not be separated from the discipline. Discipline can grow and can be applied in each of the activities when any activity comes from his heart without any coercion from anywhere. In recent years a lot of discipline of the Indonesian nation is increasingly reduced. This research. This research is quantitative. The subject of this research was the seventh grade students MTsN Megaluh 2015-2016 academic year consisting of 100 students. From the analysis stated that the respondents to the study Discipline in MTsN Megaluh category Jombang is being evidenced by the respondents of 100 respondents, or 60% of the vote with a final score of 50-63 at the interval. There is a relationship with the discipline of learning class VII student achievement MTsN Megaluh Jombang Academic Year 2015-2016. Based on the overall hypothesis testing conducted by F test, performed in accordance to the annex ANOVA F column, obtained calculated F value of 24 002 and F table with α = (0.05) df = n - k-1 = 100-1-1 = 98 so that the F table = 3.94. This value indicates that the value of F count> F table (24 002> 3.94). And hipotesin calculation by using analysis of coefficient of determination (R2) This means that there is a connection simultaneously learning Discipline (X) to the dependent variable (Y) that is Achievement for 0602 (60%). Thus, in this study we can conclude that the working hypothesis (Ha) which states: "The relationship between the discipline of learning and academic achievement of students of class VII MTsN Megaluh Jombang" acceptable ". While the null hypothesis (H0) which states: "The relationship between the discipline of learning the class VII student achievement MTsN Megaluh Jombang 2015-2016 school year '' rejected '